Fair Pay for Fair Play: Estimating Pay Equity in Professional Baseball with Data Envelopment Analysis - Howard, Larry W.; Miller, Janis L. (Academy of Management Journal, 1993)
Data envelopment analysis shows promise for generating objective estimates of pay equity. Applied to performance and salary data for 433 professional baseball players, data envelopment analysis identified objectively underpaid, equitably paid, and overpaid players. The output also identified relevant referents for each player and quantified the relative influences of referents and all variables.